The Circulation of Ideas in Firms and Markets - Hellmann, Thomas; Perotti, Enrico (Management Science, 2011)
This paper models the generation, circulation, and completion of new ideas, showing how markets and innovative firms complement each other in a symbiotic relationship. Novel ideas are initially incomplete and require further insight before yielding a valuable innovation. Finding the complementary piece requires ideas to circulate, which creates appropriation risks. Circulation of ideas in markets ensures efficient completion, but because ideas can be appropriated, market entrepreneurs underinvest in idea generation. Firms can establish boundaries that guarantee safe circulation of internal ideas, but because firms need to limit idea circulation, they may fail to achieve completion. Spin-offs allow firms to benefit from the market's strength at idea completion, whereas markets benefit from firms' strength at generating new ideas. The model predicts diverse organizational forms (internal ventures, spin-offs, and start-ups) coexisting and mutually reinforcing each other. The analysis provides new insights into the structure of innovation-driven clusters such as Silicon Valley. This paper was accepted by Bruno Cassiman, business strategy.